Annual Observations of Climatic Impacts in the Songhua River Basin, China. (10th February 2016) - Song, Xiaocheng; Jing, Liu
Abstract : Heat fluxes have been recognized as determinant regarding the river effect on microclimate. The relationship between rivers and the atmosphere is particularly significant for heat fluxes and varies with the meteorology and hydrology. In this study, based on annual observation data from the Songhua River Basin (Harbin, China), a regression and a stochastic model were used to analyze the relationship of the atmosphere-river daily maximum temperatures and evaluate the heat fluxes. The root mean square error (RMSE) of the river temperature was 2.21°C with the regression method, improving to 0.83°C with the stochastic model. The net shortwave radiation flux was the dominant heat gain component, while the latent heat flux accounted for the main heat loss. The sensible heat flux represented the smallest contribution. The river thermal effect in summer mainly resulted from the latent heat exchange, while the effect of the sensible heat exchange tended to be stronger in spring and autumn.